Radionuclide targeted therapy, theranostics, and precision medicine in the era of hybrid imaging: an important pillar in cancer care - Suppiah, Subapriya; S. Pribadi, Unfound; Sukrasno, Sukrasno (Universiti Putra Malaysia, 2022)
Cancer is one of the leading causes of death worldwide due to non-communicable diseases. In 2020, the World Health Organization reported that there were approximately 48,000 new cancer cases per year in Malaysia, the majority of which were breast cancers, followed by colorectal and lung cancers (1). Among Malaysian men, the top three cancers were lung, colorectal and prostate cancers, whereas Malaysian women succumbed mostly to breast cancer, followed by colorectal and ovarian cancers (1). The alarming rise in cancer cases makes oncology services ever more pertinent, involving a spectrum of work that translates from bench side to bedside. Hence making synergistic works by the scientists and clinicians available for cancer care.